CONTEMPORARY WOMEN ART AND ARTISTS: A STUDY ON FEW FEMALE VISUAL ARTISTS OF ASSAM - Mazinder, Dr. Raj Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Art has always been an open filled for women artists and an important tool for social and political articulation from a gender perspective, so they have expressed many forms of repression and discrimination by using various media and by incorporating both traditional and modern-day motifs. A large number of them have been active even in the pre-independence era of India, as the visibility of women-made art production grew, which can be contributed to the prominence of Sunayana Devi of famed Jorasnako Tagore residence of Calcutta and Paris educated painter Amrita Sher-Gil with their pioneering works. My objectives are to study contemporary women artists in Assam in specific of recent time of last 30 years and their concerns on globalization, gender politics and ecology of Assam.